A virtual reality-based pre-discharge home assessment for inpatient rehabilitation: co-creation, feasibility and user perception - Kirchner-Heklau, Uta; Saal, Susanne (BMC Digital Health, 2025)
Background Pre-discharge home assessments (PDHAs) in inpatient rehabilitation help healthcare professionals evaluate patients’ home environments before discharge, ensuring accessibility, safety, and independent living. These visits improve patient adherence to recommendations and patient involvement but are resource-intensive. Ward based assessments using a virtual representation of the patient´s home might overcome these obstacles. This study aims to develop and test a virtual reality (VR)-based PDHA prototype based on healthcare professionals’ (HCP) needs, assessing its impact on therapy and home adaptation planning from both provider and patient perspectives. Results In the needs assessment and prototyping phase, a VR-based home environment assessment tool (VR PDHA) was developed based on feedback from HCPs such as physiotherapists and occupational therapists. The tool was developed to assess patients’ home environments, measure rooms and share information. The IT infrastructure consisted of a smartphone with LIDAR technology and an app for scanning and exporting the data to a content management system, where the data can be calculated and edited. Users can also navigate, measure, comment and export spatial data at the frontend and also move around and measure in the VR environment. The intervention was tested in a real-world setting with 12 patients. Feedback showed that the VR tool improved communication, supported discharge planning and improved understanding the challenges at home. While therapists rated the usefulness of the tool highly, some patients had difficulty visualising the changes. Overall, the intervention supported the therapeutic goals and provided workable recommendations for home adaptations and aids. Further technical improvements were suggested to increase its usefulness. Conclusions This study demonstrates the development of a VR PDHA, which is accepted by users. The prototype exceeds the capabilities of existing virtual home assessment applications. It provides benefits of a home visit without necessitating extensive personnel or time resources, thereby enhancing both counselling and the provision of aids and modifications. The previously unconsidered user requirements of other user groups outside the rehabilitation clinic, who are also involved in the PDHA process, offer potential for the technical expansion of future prototypes. Trial registration Study registration of the pilot study occurred prior to inclusion of the first study participant as DRKS00025836 on August 24, 2021 in a publicly accessible study registry (German Clinical Trials Register).